Myocardial Injury Predicts Risk of Short-Term All-Cause Mortality in Patients With COVID-19: A Dose–Response Meta-Analysis - Li, Yuehua; Pei, Hanjun; Zhou, Chenghui; Lou, Ying (Frontiers in Cardiovascular Medicine, 2022)
Objective: Predictive value of myocardial injury as defined by elevated cardiac tropnins (cTns) in COVID-19 patients has not been fully investigated. We performed a meta-analysis to evaluate the dose-response relationship between myocardial injury and short-term all-cause mortality. Methods: Pubmed, Embase and the Cochrane Library database were searched for all the studies which evaluated the relationship of cTns and the risk of short-term all-cause mortality in COVID-19 patients. Results: Compared with patients without myocardial injury, the group with elevated cTns was associated with increased short-term mortality (11 studies, 29 128 subjects, OR 3.17, 95% CI 2.19 to 4.59, P = 0.000, I2 = 92.4%, P for heterogeneity 0.00). For the dose-response analysis, elevation of cTns 1x99th percentile upper reference limit (URL) was associated with increased short-term mortality (OR 1.99, 95% CI 1.53 to 2.58, P = 0.000). The pooled OR of short-term mortality for each 1xURL increment of cTns was 1.25 (95% CI 1.22 to 1.28, P = 0.000) Conclusion: We found a positive dose-response relationship between myocardial injury and the risk of short-term all-cause mortality, and propose elevation of cTns > 1x 99th percentile URL was associated with the increased short-term risk of mortality.